Problems of the legal adjusting of access to confidential information on an enterprise - Нашинець-Наумова, А. Ю. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Concept «confidential information» is investigational in the article, «commercial secret», the legal aspectsof defense of such type of information are analyzed on enterprises.